Ion mobility-mass spectrometry shows stepwise protein unfolding under alkaline conditions. Issue 12 (13th January 2021) - Sahin, Cagla; Österlund, Nicklas; Leppert, Axel; Johansson, Jan; Marklund, Erik G.; Benesch, Justin L. P.; Ilag, Leopold L.; Allison, Timothy M.; Landreh, Michael
Abstract : Although native mass spectrometry is widely applied to monitor chemical or thermal protein denaturation, it is not clear to what extent it can inform about alkali-induced unfolding. Abstract : Although native mass spectrometry is widely applied to monitor chemical or thermal protein denaturation, it is not clear to what extent it can inform about alkali-induced unfolding. Here, we probe the relationship between solution- and gas-phase structures of proteins under alkaline conditions. Native ion mobility-mass spectrometry reveals that globular proteins are destabilized rather than globally unfolded, which is supported by solution studies, providing detailed insights into alkali-induced unfolding events. Our results pave the way for new applications of MS to monitor structures and interactions of proteins at high pH.